EVALUASI PERFORMA SUMUR MINYAK DENGAN MASALAH POUR POINT DI LAPANGAN X - Faiz, Usman
Field X is an oil well that has been producing since 1972, it consist of 265 wells which produces oil and gas, Two production wells had been reproducing in 2014 with new perforated zone, its has high pour point oil problem. High pour point oil is a factor that influence the performance rate of the well. In this study the pour point problem is identified by evaluating the oil well performance, the evaluation of oil well performance is done by using the nodal analysis matching between the real oil well condition with simulation condition in PROSPER software. Then the production history of the well is evaluated. The evaluation of the crude oil properties is done by laboratory test to get the API and pour point value. Then the study continue by evaluating the temperature profile and pressure profile along the flowline by using PIPESIM software. Some solution of the problem is proposed ,the first is by using chemical compound pour point depressant that took laboratory test to get the optimum dosage. The second solution is by producing the well with commingle flowline, the sensitivity of the rate is done to get the temperature profile and pressure profile. The third solution is by dilluting the oil with the low pour point oil, and the last is